2020
DOI: 10.1021/acs.energyfuels.0c02803
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Evaluation of Hybrid Gas Hydrate Inhibition Strategies

Abstract: In subsea oil and gas production, a transition away from complete gas hydrate avoidance to riskbased hydrate management has the potential to offer cost savings and improved viability for new developments. Rigorous characterization of hydrate formation probability (via the measurement of statistically significant numbers of independent hydrate formation events) represents a critical step towards accurate quantification of hydrate blockage risk. Such characterization is especially pertinent when deploying low do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…When treated as a single dataset, the data from the low concentration mixtures are referred to as 59 ppm (the arithmetic mean of these concentrations). Bin widths were selected such that the resultant histograms exhibit a monotonic increase and decrease on either side of the mean subcooling, based on previous work in which greater numbers of formation events were used to generate the histograms 36,46,47 . Accordingly, the choice of bin width, δ T f , varies slightly between each dataset: In Figure 6, (a) δ T f = 1.5 K (59 ppm), (b) δ T f = 1.25 K (100 ppm), and (c) δ T f = 1.75 K (500 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When treated as a single dataset, the data from the low concentration mixtures are referred to as 59 ppm (the arithmetic mean of these concentrations). Bin widths were selected such that the resultant histograms exhibit a monotonic increase and decrease on either side of the mean subcooling, based on previous work in which greater numbers of formation events were used to generate the histograms 36,46,47 . Accordingly, the choice of bin width, δ T f , varies slightly between each dataset: In Figure 6, (a) δ T f = 1.5 K (59 ppm), (b) δ T f = 1.25 K (100 ppm), and (c) δ T f = 1.75 K (500 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…While nucleation rates at constant temperature can be determined by fitting induction time formation probabilities to Equation (), such measurements are slow and limited in their ability to efficiently probe how J varies with subcooling. The measurement of solid formation along constant‐cooling ramps can more efficiently provide information about the dependence of nucleation rate on subcooling if analyzed correctly 46 . Recently, Barwood et al 36 demonstrated an efficient method of extracting methane hydrate nucleation rates from formation data measured along constant cooling ramps that were equivalent to those determined by constant temperature experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past three years, an array of these HPS-ALTA cells have been used to record thousands of hydrate formation events, across the range of accessible shear rates and compositions. , Efforts by Metaxas et al configured these cells to study induction time, which enabled a new probabilistic input for field-scale simulation with the above-described mechanistic model; the most recent efforts by Lim and co-workers , and Barwood et al have extended this induction time approach to study various KHIs as a function of concentration, with suggestions that systems containing KHI may not follow classical nucleation theory, which the HPS-ALTA system successfully established for pure guest–water systems . Together, the unique experimental capability and mechanistic model provide a means by which both the probability and severity of a hydrate formation event may be calculated.…”
Section: Structure–function Inhibitor Developmentmentioning
confidence: 99%
“…As introduced above, the development pathway of low-dosage hydrate inhibitorsKHIs and AAshas historically relied on rocking cell tests, which are only able to provide binary assessments of inhibitor effectiveness (i.e., the hydrate was or was not sufficiently severe as to prevent the ball from traversing the volume); such a method constrains insight into how nuanced changes to inhibitor molecules affect performance, and consequently limits the resolution by which research laboratories can compare new chemical inhibitor designs or solvation packages. The HPS-ALTA approach described above is one such example of high-fidelity KHI assessment, enabling new insight as to the molecular mechanism(s) , responsible for KHI performance; this method further enables a new generation of structure–function assessment, whereby the effect of minor structural variations on KHI performance can be optimized against ecotoxicity, biodegradability, bioaccumulation, or other key metrics.…”
Section: Structure–function Inhibitor Developmentmentioning
confidence: 99%